Anterolateral Thigh Flap for Abdominal Wall Reconstruction: A Lifesaving Procedure—A Case Report - N. Nagaprasad; G. Praveen Harish; Asmat Jahan; Kavya Gaddam; Satwika Dharanikota (Indian Journal of Plastic Surgery)
It is extremely challenging to deal with a complex full-thickness abdominal wall defect following serious trauma. We aim to share our experience in applying an anterolateral thigh flap in abdominal wall defect reconstruction. This is a retrospective case report of a 40-year-old male patient with a large area of full-thickness defect in the abdominal wall complicated with multiple organ damage identified due to acute trauma. Immediate organ repair surgeries were performed. Meanwhile, the patients underwent complete debridement in the zone of the abdominal wall defect, together with negative pressure wound therapy. Then the appropriate timing was chosen to perform a pedicled anterolateral thigh flap with vastus lateralis muscle for reconstructing a large area of full-thickness defect involving the abdomen. The outcome of the patients was also good. Thus, we conclude that the pedicled anterolateral thigh flap and vastus lateralis muscle flap are feasible to repair full-thickness defect in the abdominal wall and serve as lifesaving options.